QUALITY FUNCTION DEPLOYMENT FOR BIO PLASTICS ADOPTION IN MALAYSIAN INDUSTRY - bin Ahmad Shamsuddin, Don Mardzi; Chew, Boon Cheong; Heoy Shin, Loo (Journal of Technology Management and Business, 2015)
Plastic have transformed our everyday life and their usage is increasing and about 50 percent of plastics is used for single-use disposable applications. However, carbon-based plastics have brought a lot of environmental issues, such as global warming, greenhouse effect and air pollution. Hence, the introduction of bio plastics is launched and this plastic is manufactured from renewing raw materials which may help lower the dependency on mineral fuels and plastics waste. Quality Function Development (QFD) model is the technique that based on the analysis of the clients’ requirements which normally are expressed in qualitative terms. QFD is divided into four phase: product development, product design. Process preparation and process control. Customers are looking for substitute of petrochemical plastics due to the concern of the nature that petrochemical plastic when disposed of and burned can release toxic pollutants. Besides think of the raw materials used, European also consider about the sustainable food chain from bio plastic. After getting the customer requirements, QFD led to study on the characteristics of bio plastic. This step is to understand how the need can be satisfied  and ask ‘why; until the truly understand what the root need. Further on, the degree of correlation between the selected characteristics was evidenced in the correlation matrix. The characteristics that taking account refer to the commodity and comfort in use, the shape of the package, temperature at distribution, trade mark, labeling and the possibility to correlate the ration price/ quantity. As awareness in using bio plastics can be witnessed in many developed countries where a wide range of favorable initiatives are put in action, including government policies, research and development and the industrial promotion.